Multi-modal Vortex-Induced Vibrations of a vertical riser pipe subject to a uniform current profile - Willden, Richard H.J.; Graham, J.Michael R. (European journal of mechanics, B, Fluids, 2004)
The transverse Vortex-Induced Vibrations of a long (length to diameter ratio, L/ D=1544), flexible pipe, that was subjected to a uniform current profile (Reynolds number, Re=2.84×10 5) have been simulated using a strip theory Computational Fluid Dynamics model. The pipe's mass ratio (the ratio of the pipe's mass to the mass of fluid displaced by it) was varied between 1.0 and 3.0 in order to study its effect upon the vibrational behaviour of the pipe. Despite the inflow current being uniform the pipe was observed to vibrate multi-modally. Furthermore, all of the excited modes vibrated at the excitation (Strouhal) frequency. The fluid, via its added mass, was found to be able to excite modes whose natural frequencies differed from the excitation frequency. This ability was observed to decrease with increasing mass ratio.